The effective volumes of waters of crystallization & the thermodynamics of cementitious materials - Glasser, Leslie (2021)
Hydrates are significant components of cements and concrete. We examine the effective volumes of waters of crystallization for these materials, where the “effective volumes” are the difference per water molecule between the formula volume of the hydrate and of its parent anhydrate. These effective volumes cover a small range around 15 cm3 mol−1 (≅ 23 Å3 per water molecule), unlike the wider range for general inorganic materials.